Mechanisms for destabilisation of RNA viruses at air-water and liquid-liquid interfaces - C. A. Brackley (Nature Portfolio, 2021)
We know that air-water interfaces can generically inactivate viruses, but the mechanisms behind this observation are unclear. Here the authors use simulations to uncover those mechanisms and find that the electrostatic repulsive free energy of an RNA virus increases by several thousands of kBT as it approaches an air-water interface, providing a mechanism for viral destabilization which may induce inactivation.